Factors that influence female students in purchasing skin care product in the University of Mindanao Digos College - Gonzales, Kwinny Pearl; Patentis, Anna Marie F.; Paller, Nina Jean T. (--Digos City: UM Digos College, 2017)
The study was conducted to determine the factors that influence female student's purchasing skin care products in the University of Mindanao Digos College. In view of this, there were relative question that would be the basis in achieving the research purpose. These question were about the factors that influence female students in purchasing skin care product in term of price, brand name and product quality and which among the factors really influence female students to purchase skin care products in University of Mindanao Digos College. The researchers used the descriptive-correlational design. With three hundred as the count of the female students presently enrolled at the University of Mindanao Digos College are willing to answer. The null hypothesis was tested at 0.05 level of significance. Our study shows that product quality was necessary for the female students to purchase skin care products of their choice and preference. On the other hand quality attributes or product quality refers to the cues that could be used by consumers to infer some expected experience product quality. The overall result factors that influence female students skin care products purchasing in Digos College is high.